Ethnographic Blogging: Reflections on a Methodological Experiment - Tocci Jason (Cultural Science)
This paper describes how a weblog was utilized as a major component in a long-term, multi-site ethnography with both “virtual” and physically situated research components. “Ethnographic blogging” describes not only the act of writing on a website and hoping that someone will read it, but the process of regularly maintaining a blog, and the modes of interaction and observation that this process gradually enables. In my own study of self-identified ‘geeks’ and ‘nerds,’ ethnographic blogging involved traversing news sites, forums, and other blogs for relevant content, leading to opportunities for dialogue with other bloggers and readers; establishing a persona online as a researcher, which has encouraged subjects to invite me to public and private discussions about their culture and identities; and bringing together online subjects from multiple physical sites, among other opportunities. My own experience of integrating a blog into ethnographic research was largely experimental, though I offer these reflections to encourage researchers to consider what alternative means of qualitative analysis online may have to offer us.